Analysis of Methods of Sinking Alloys on the Surface of Items - Xolmo’minova Dilrabo Axmatqul qizi (Peerian Journals Publishing, 2022)
Based on the chemical precision of metals, the oxidation reaction of the dissolved returner lies in the electrolyte, resulting in the return of metal on a catalytic active surface free of electrons. The more positive the standard potential of metal, that is, the more non-metallic it is, the wider the ability to choose a returner. The main condition for the reaction to occur is its autocatalytic character, which means that the sedimentation metal will depend on its ability to catalytically accelerate the return process.
Keywords: electrolyte; decorativ; antifriction; potential